Ethos et blog d’écrivain : le cas de L’Autofictif d’Éric Chevillard - Ugo Ruiz (Contextes)
This article examines the characteristics of the online construction of a writer’s self-image, through the study of Eric Chevillard’s blog L’Autofictif. By writing a blog, an author doesn’t invest a ‘genre’ as conceived in the editorial system, but a formal mold that precisely questions the notion of text. Digital writing also affects the status of the author, given the fact that the writer communicates directly with the readers of his blog, and can thus construct his own frame of legitimation. On the basis of concepts from discourse analysis (Maingueneau, Amossy), it is shown how Chevillard makes use of his status as an established writer to construct his legitimacy online. Through irony, metadiscursive statements, declarations of literary friendship and critical standpoints, his blog offers a definition of the ‘real’ writer and of ‘good literature’. Meanwhile, the author status of Chevillard gives his blog a literary dimension, something that anonymous authors cannot do because they lack an author image established by others.